Spatial Patterns of Dengue Hemorrhagic Fever (DHF) Cases in Boalemo Regency, 2021-2024 - Stela Puspita Latowa; Herlina Jusuf; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in tropical regions, with high morbidity and mortality rates. In Boalemo Regency, Gorontalo Province, DHF cases increased from 2021 to 2024, with a total of 536 cases and 10 deaths. This condition is suspected to be influenced by environmental factors, including population density, air temperature, and rainfall. This study aimed to analyze the spatial distribution patterns of DHF cases and their relationship with environmental factors. This study employed a quantitative approach with spatial analysis based on Geographic Information Systems (GIS). Data were obtained from relevant institutions, with a sample of 230 DHF cases. The analysis included mapping case distribution, Spearman's Rank correlation test, and Moran's Index calculation to identify spatial endemicity patterns. The findings indicated that population density had no significant association with DHF cases (p = 0.538>0.05). Conversely, air temperature showed a significant positive association with DHF cases (p = 0.024 <0.05). Rainfall also demonstrated a significant positive association with DHF cases (p < 0.05). In conclusion, this study highlights the role of climatic factors, particularly rainfall, in the increase of DHF cases in Boalemo Regency. These findings may serve as a basis for local governments to develop more effective DHF prevention and control strategies by considering environmental and climatic factors. Keywords: rainfall, dengue hemorrhagic fever, population density, spatial pattern, air temperature